2010
DOI: 10.1016/j.neuroimage.2009.08.062
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of fiber tracking measurements in diffusion tensor imaging for longitudinal study

Abstract: The statistical reliability of diffusion property measurements was evaluated in ten healthy subjects using deterministic fiber tracking to localize tracts affected in motor neuron disease: corticospinal tract (CST), uncinate fasciculus (UNC), and the corpus callosum in its entirety (CC), and its genu (GE), motor (CCM), and splenium (SP) fibers separately. Measurements of fractional anisotropy (FA), mean diffusivity (MD), axial diffusivity (λ 1 ), transverse diffusivity (λ ⊥ ), and volume of voxels containing f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
82
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(95 citation statements)
references
References 70 publications
11
82
0
2
Order By: Relevance
“…DTI may be a promising marker to follow longitudinal changes in white matter tracts in normal aging and neurodegenerative diseases. However, for longitudinal studies to be feasible, it is imperative to establish that DTI measurements can be made reliably on individual subjects [Danielian et al, 2010].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DTI may be a promising marker to follow longitudinal changes in white matter tracts in normal aging and neurodegenerative diseases. However, for longitudinal studies to be feasible, it is imperative to establish that DTI measurements can be made reliably on individual subjects [Danielian et al, 2010].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies investigated reliability by performing repeated scans on a few subjects acquired within the same scan session or within short scan intervals. This approach may underestimate the sources of variability relevant for longitudinal studies (e.g., scanner drift) [Danielian et al, 2010]. To our knowledge, there have been no studies that evaluated intra-scanner or inter-scanner reliability using longitudinal data obtained on a large number of subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Методы тракто-графии позволяют визуализировать архитектуру волокон, идентифицировать количество, объем, направление волокон, что представляет опреде-ленный интерес в процессе отслеживания восста-новления нервного тракта. Хотя трактография яв-ляется проверенным методом диагностики постин-сультных нарушений [26,27], различные методы анализа могут влиять на интерпретацию результа-тов [27]. Auriat и соавторы выявили, что ДВМРТ и метод ограниченной сферической деконволюции (ОСД) показывают разные результаты у пациентов в хроническую стадию инсульта [28].…”
Section: V8motors@ukrnetunclassified
“…On the midsagittal slice another ROI is drawn around the splenium of the corpus callosum (F). the scope of this work (e.g., Ciccarelli et al, 2003;Danielian et al, 2010;Malykhin et al, 2008;Pfefferbaum et al, 2003). For each reconstructed fiber bundle, average FA, MD, AD, RD, and tract volume were computed.…”
Section: Fiber Tractographymentioning
confidence: 99%
“…By combining objective protocols for extracting WM fiber pathways of interest on the one hand (Catani and Thiebaut de Schotten, 2008;Wakana et al, 2004Wakana et al, , 2007 and incorporating subjective prior knowledge from the neuroanatomical expert on the other hand, many studies have already demonstrated the high inter-and intrarater reliability and scan-rescan reproducibility of manual FT segmentations (Ciccarelli et al, 2003;Danielian et al, 2010;Heiervang et al, 2006;Kristo et al, 2013,in press;Malykhin et al, 2008;Pfefferbaum et al, 2003;Wakana et al, 2007). The major drawback of manual FT segmentations, however, is that placing ROIs for tract selection can be very labor-intensive and time-consuming, whichfor obvious reasons -can become problematic for large-cohort studies.…”
Section: Introductionmentioning
confidence: 99%